The composite cost function and efficiency in giant Japanese banks - McKillop, Donal G.; Glass, J.Colin; Morikawa, Yukio (Journal of Banking & Finance, 1996)
This study provides further empirical investigation, in the context of giant Japanese banks, of the recent claim by Pulley and Braunstein (1992, A composite cost function for multiproduct firms with an application to economies of scope in banking, Review of Economics and Statistics 74, 221–230), that their new composite model for the multiproduct cost function has important advantages over the separable quadratic, generalized translog and standard translog models. In addition to assessing the composite model's relative ability in measuring global scope and scale economies, the study also extends the P-B analysis to assess measurement of product-specific scope and scale economies, pairwise cost complementarities between outputs, changes in the marginal costs of outputs and technological change. The results appear to confirm P-B's chain. The persistent finding of scale economies for large Japanese banks is also investigated and confirmed.